Mesozooplankton biomass, grazing and trophic structure in the bluefin tuna spawning area of the oceanic Gulf of Mexico. (10th March 2021) - Landry, Michael R; Swalethorp, Rasmus
Abstract: We investigated size-fractioned biomass, isotopes and grazing of mesozooplankton communities in the larval habitat of Atlantic bluefin tuna (ABT) in the oceanic Gulf of Mexico (GoM) during the peak spawning month of May. Euphotic-zone biomass ranged from 101 to 513 mg C m −2 during the day and 216 to 798 mg C m −2 at night. Grazing varied from 0.1 to 1.0 mg Chl a m −2  d −1, averaging 1–3% of phytoplankton Chl a consumed d −1 . Carnivorous taxa dominated the biomass of > 1-mm zooplankton (78% day; 60% night), while only 13% of smaller zooplankton were carnivores. δ 15 N enrichment between small and large sizes indicates a 0.5–0.6 trophic-step difference. Although characteristics of GoM zooplankton are generally similar to those of remote oligotrophic subtropical regions, zooplankton stocks in the ABT larval habitat are disproportionately high relative to primary production, compared with HOT and BATS averages. Growth-grazing balances for phytoplankton were resolved with a statistically insignificant residual, and trophic fluxes from local productivity were sufficient to satisfy C demand of suspension feeding mesozooplankton. While carnivore C demand was met by local processes in the central GoM, experiments closer to the coastal margin suggest the need for a lateral subsidy of zooplankton biomass to the oceanic region.